Breast size impact on adjuvant radiotherapy adverse effects and dose parameters in treatment planning - Ratoša, Ivica (Radiology and oncology (Ljubljana), 2018)
Breast radiotherapy is an established adjuvant treatment after breast conserving surgery. One of the important individual factors affecting the final cosmetic outcome after radiation is breast size. The purpose of this review is to summarise the clinical toxicity profile of adjuvant radiotherapy in women with breasts of various sizes, and to evaluate the treatment planning studies comparing target coverage and dose to thoracic organs at risk in relation to breast size.
Keywords: dojke; neželeni učinki; obsevanje; rak (medicina); velikost obsevanega volumna